Constructing a Saint’s Life between Rome and the Provinces: Jesuit Hagiographical Literature on Peter Canisius - Friedrich, Markus (Journal of Jesuit studies, 2023)
There is general agreement about the Jesuits’ alertness to media, their crucial role in early modern printing, and their engagement in promoting the sanctity of some of their members through print publication. Despite several efforts to establish central control, most of the Society’s media production remained decentralized. Moreover, there was no pre-conceived publication strategy of hagiographical activities. As a result, the production of hagiographies often sprung up locally and with little initial awareness of each other. Hence, it was nearly unavoidable that projects overlapped and that competition between them arose. Examining two early hagiographic accounts of the life of Peter Canisius, the article sheds light on the Jesuits’ production and publication of hagiographical literature by linking the publication history of both projects to an investigation of the underlying manuscripts. As the paper demonstrates, early modern Jesuit print and manuscript culture cannot be separated.